SAT0318 Do patients in remission in psoriatic arthritis, have less fatigue? and does this depend on the definition of remission? an analysis of 304 patients. (12th June 2018) - Gorlier, C.; Puyraimond-Zemmour, D.; Kiltz, U.; Orbai, A.-M.; Leung, Y.Y.; Palominos, P.; Cañete, J.D.; Scrivo, R.; Balanescu, A.; Dernis, E.; Talli, S.; Ruyssen-Witrand, A.; et al.
Abstract : Background: Fatigue is a critical element of life impact for patients with Psoriatic Arthritis (PsA) and is not considered in remission definitions. In PsA, remission can be defined using composite scores (Minimal Disease Activity (MDA), Disease Activity in PSoriatic Arthritis (DAPSA)≤4), Patient Acceptable Symptom State (PASS), Patient Global Assessment (PGA)(for example ≤1/10), or as a single for remission item. Objectives: To explore the relationship between fatigue and remission in PsA, when using different definitions of remission. Methods: ReFlaP (NCT03119805 ) is a cross-sectional study in 14 countries of consecutive adult patients with definite PsA and more than 2 years of disease duration. Patient-perceived fatigue was assessed by a 11-point numerical rating scale. Remission status was defined from the physician's perspective as MDA, DAPSA≤4 and physician-perceived remission (single question yes/no), and from the patient's perspective as PASS, PGA ≤1 and patient-perceived remission (single question yes/no). We calculated fatigue group means and deltas by remission status and compared these by Student's t test. For known groups validity of each remission definition we used ROC curves and corresponding areas under the curve (AUC). Results: Of 366 patients, 304 had both fatigue and remission data available: 148 (49.8%) were male, mean age was 53.9±12.3 years, mean disease duration was 10.8±7.7 years; 90.3% had predominant peripheral disease, 56.3% were taking methotrexate, 66.5% a biologic and 19.4% oral glucocorticoids. Disease activity was moderate: 41.1% had no current psoriasis skin lesions, mean Tender Joint Count (TJC) was 4.3±8.9, mean Swollen Joint Count (SJC) was 2.66±8.3, mean Physician's global assessment was 3.0±2.4, mean PGA was 4.19%±2.7. 80.6% patients had DAPSA levels<28 (ie, remission, low or moderate disease activity).Mean patient's assessment of fatigue was 4.26±3.0. The frequency of remission varied from 17.4% to 64.8% (the most stringent definition being DAPSA and the least PASS). Fatigue levels were much lower in remission than non-remission with group differences in fatigue ranging from 1.66±0.3) (Physician remission single question yes/no) to 3.81±0.3 (DAPSA remission) (all p<0.0001) (figure 1). Corresponding AUCs ranged from 0.66 (Physician's remission question) to 0.87 (DAPSA). Conclusions: Fatigue levels were relatively high in these PsA patients whose disease was often well-controlled. Fatigue was lower in patients in remission, according to all definitions of remission; the remission definition with best known-groups validity for fatigue was DAPSA remission. Moreover both composite measures perform better than the physicians opinion of remission. These elements may be important in a context of shared decision-making. Acknowledgements: This study was funded by Pfizer. Disclosure of Interest: None declared